2015
DOI: 10.1038/jid.2014.366
|View full text |Cite
|
Sign up to set email alerts
|

Beyond BRAF V600 : Clinical Mutation Panel Testing by Next-Generation Sequencing in Advanced Melanoma

Abstract: The management of melanoma has evolved due to improved understanding of its molecular drivers. To augment the current understanding of the prevalence, patterns, and associations of mutations in this disease, the results of clinical testing of 699 advanced melanoma patients using a pan-cancer next generation sequencing (NGS) panel of hotspot regions in 46 genes were reviewed. Mutations were identified in 43 of the 46 genes on the panel. The most common mutations were BRAFV600 (36%), NRAS (21%), TP53 (16%), BRAF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
112
1
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 131 publications
(130 citation statements)
references
References 37 publications
14
112
1
3
Order By: Relevance
“…Many studies have revealed that the BRAF mutation is associated with younger age, nodular or superficial spreading histological type, tumour location on the trunk and intermittent sun exposure (5,15,17,20). Also, a study by Hughahl et al (22) revealed the association between higher rates of BRAF V600 immunohistochemistry expression and increased tumour thickness, presence of ulceration and higher rates of mitosis.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have revealed that the BRAF mutation is associated with younger age, nodular or superficial spreading histological type, tumour location on the trunk and intermittent sun exposure (5,15,17,20). Also, a study by Hughahl et al (22) revealed the association between higher rates of BRAF V600 immunohistochemistry expression and increased tumour thickness, presence of ulceration and higher rates of mitosis.…”
Section: Discussionmentioning
confidence: 99%
“…17 Approximately 40-50 % of cutaneous melanomas have a constitutive activating mutation in BRAF V600 . 18,19 Selective small molecule inhibitors, vemurafenib and dabrafenib, are available and have been shown to postpone disease progression in patients with metastatic melanoma and an identified BRAF V600 mutation. 20 A phase 3 randomized controlled study comparing vemurafenib to standard chemotherapy (dacarbazine) demonstrated a significant survival advantage at 6 months (84 vs. 64 %) with response rates of 48 versus 5 %.…”
Section: Acquired/somatic Mutationsmentioning
confidence: 99%
“…Limited small individual trials showed that BRAF K601E and L597Q are at least partially sensitive to trametinib (MEK inhibitor), with 3 of 5 treated patients showing objective clinical and radiological response with a very manageable toxicity profile [51]. Similarly, another study including 45 patients with advanced/metastatic BRAF V600R mutant melanoma showed an overall response rate of 50% for the whole population, with a progression-free survival of 5.5 months [52].…”
Section: -16 Days >Q30mentioning
confidence: 99%
“…Although promising for BRAF V600E and K, there are very limited findings for BRAF inhibitors in melanomas harboring non-BRAF V600E mutations, which include BRAFV600R, BRAFV601K, and BRAF L597K [51,52]. Limited small individual trials showed that BRAF K601E and L597Q are at least partially sensitive to trametinib (MEK inhibitor), with 3 of 5 treated patients showing objective clinical and radiological response with a very manageable toxicity profile [51].…”
Section: -16 Days >Q30mentioning
confidence: 99%